Pengembangan Produk dan Analisis Sensori Abon Bandeng dengan Substitusi Bonggol Pisang Ulin di Kabupaten Sidoarjo, Indonesia - Sekar Ayu Wulandari; Akbar Maulana Firmansyah; Dini Nafisatul Mutmainah; Taufiq Rahman Humaidi; Fairuz Nadhifah; Imaroh Nurul Izzah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2026)
This study developed an innovative shredded milkfish product (abon bandeng) incorporating banana pseudostem (bonggol pisang ulin) in Sidoarjo Regency. Although local milkfish production and available banana biomass are substantial, empirical evidence on hybrid formulations combining animal protein and pseudostem-derived fiber, along with market-based price assessment, remains limited. The study therefore aimed to (1) develop and select the optimal milkfish: banana pseudostem formulation for sensory acceptance, (2) identify the consumer preference drivers for the selected product, and (3) assess preliminary commercial viability using the Price Sensitivity Meter (PSM). Four formulations (100:0, 70:30, 50:50, 30:70) were evaluated via organoleptic testing with 70 respondents; subsequent consumer preference and PSM analyses were conducted. The 50:50 formulation achieved the highest acceptance (mean = 4.014; like rate = 81.43%). ANOVA showed significant differences (p < 0.05) in aroma, texture, and taste across formulations. PSM indicated an acceptable price range of IDR 14,500–20,000 and an optimal price point at IDR 15,500. Taste and nutritional value were key purchase drivers (88.6%), and online marketplaces were the principal distribution channel (45.7%). Findings demonstrate sensory viability and preliminary commercial potential for this hybrid product. This study contributes by integrating sensory optimization and price modeling into hybrid animal–plant product development, while providing an empirically validated formulation and an optimal pricing reference to support circular-economy-based agro-innovation.